Exploring coping among urban youth through photovoice. (November 2018) - Rose, Theda; Sharpe, Tanya L; Shdaimah, Corey; deTablan, Dante
Adolescent perspectives on coping are often explored through quantitative methods within a problem-focused paradigm. To better understand how urban adolescents define, perceive, and experience coping, this research used photovoice, a qualitative research method that employs co-creation of meaning and knowledge around photographic images. Twelve adolescents in the 9th-11th grades at a Baltimore City High School photographed images representing coping. They participated in focus groups to discuss how their pictures reflected coping and its relationship to decision-making, development, and academic success. Participants identified different types of coping, as well as strategies and resources in their homes, school, and community. They classified coping as "good" or "bad, " depending on its impact on themselves and others. They described how coping evolves and noted long-term consequences of different coping strategies, suggesting a future-oriented aspect to their understanding of the concept. Students presented these findings to key stakeholders including a congressional representative, the Baltimore City School Board, community members, and their peers. Study findings elucidate the importance of adolescent perspectives to the coping research literature. Moreover, findings can inform the development of school and community-based programs designed to foster coping among urban adolescents.